Handbook of Integrative Dermatology An Evidence-Based Approach - Lio, Peter A.; Patel, Toral; Peters, Neill T.; Kasprowicz, Sarah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This user-friendly reference tool presents clinical scenarios and discusses some practical complementary and alternative therapies available in dermatology. It focuses on peer-reviewed data that are suitable for use in a conventional dermatology practice and helps dermatologists guide their patients when faced with questions regarding integrative dermatology using an evidence-based, reader-friendly, and case-focused approach. Within the field of dermatology, there is a marked void in the understanding of complementary and alternative approaches, though dermatologists frequently use off-label therapies to manage chronic conditions. They do so, however, with a range of success and potentially considerable side effect profiles. Handbook of Integrative Dermatology is a must-have tool for any practicing dermatologist.
Keywords: Dermatology; Complementary medicine; Dermatology; Complementary & Alternative Medicine